Impact of Integrated Home-Based Care Programme on Antiretroviral Medication Adherence among Plwha: A Quasi-Experimental Study. - Solomon Joseph Chiegil; Nnodimele Onuigbo Atulomah; Umeh, Mercy Orji; Ogechukwu, Emmanuel, OKONDU; Joseph Emmanuel Chiegil (Student's Journal of Health Research, 2022)
Background: Suboptimal Anti-Retroviral adherence is an advancing global issue.  Methodology: One-Group Pre- and Post-Test Integrated Home-Based Care intervention program with control was adopted. The validated questionnaire was used to gather information from 60 PLWHA following ethical approval and informed consent. Descriptive statistics and frequency distributions are employed in data analysis. One-tailed independent sample T-test was used to determine the impact of the intervention using percentage-change and Cohen's Effect Size with a 5% level of significance. Validity and reliability of Instrument tested with Cronbach Alpha, 0.795. Results:  Respondents mean age was 35.38 ± 9.061, married (37.61%), females (66%) and self -employed (41.1%). Mumuye ethnic group (28.3%), Christians, 71.7% with lower educational attainments (56.6%). Control group reported predisposing factors in HIV treatment (137-point scale),  = 82.17(2.18) ±11.92 and  = 86.50(1.69) ±9.23; Reinforcing factors on 15-points scale, scored  = 9.00(0.65) ±3.65 and  = 8.87(0.69) ±3.78; Enabling factors on 15-points scale,  = 8.23(0.46) ±2.50 and  = 8.00 (0.51) ±2.77 and Self-Reported Adherence on 24-points scale,  = 16.23(0.82) ±4.49 and  = 17.87(0.91) ±4.99 at baseline and post intervention respectively for each group and adherence prevalence rate of 60.  Experimental group at baseline reported predisposing factors on 137-points scale,  = 80.90(2.77) ±15.15 and  = 97.13(8.12) ±1.48; Reinforcing factors on 15-points scale,  = 8.87(0.47) ±2.50 and  = 9.33(0.48) ±2.60; Enabling factors on 15-points scale,  = 7.23(0.41) ±2.24and  = 7.40(0.41) ±2.25 and Self-reported Adherence on 24-points scale,  = 15.98(0.57) ±4.39 and  = 23.13(0.43) ±2.37 at baseline and post intervention respectively for each group and adherence prevalence rate of 96%.  Conclusion: An integrated Home-Based Care intervention program will be more effective than the usual clinic-based program for HIV/ AIDS management. Recommendation:  An integrated Home-Based Care intervention program should be adopted for all HIV interventions.